Apollonius Rhodius Argonautica 4 and the epic gaze: there and back again - Lovatt, Helen (De Gruyter, 2018)
The visuality of Apollonius Argonautica is complex and fascinating, and important for understanding that of later Greek and Roman epic. The Argonautica features in The Epic Gaze as the epic that wouldn't, a refusenik of the epic genre, a counterexample. This chapter explores the particular visuality of Apollonius in more depth, by focusing on book 4 and its continuities and divergences from the previous books. In this chapter I re-examine gaze and vision in Apollonius by thinking about the difference between the explorers' gaze and the colonial gaze, between the outward journey and the return, between the Argonauts as objects and subjects. To what extent are the Argonauts a force for order, distinguishable from Herakles as a bringer of chaos? The chapter also re-evaluates the significance of the divine gaze in book 4, where it takes on a new prominence, and explore the epiphanies of book 4. Much of the action in book 4 takes place in darkness, and the chapter investigates the effects of this darkness. How does failure of the gaze relate to narrative control? How does the Argonautica's play with different levels of knowledge and information relate to its exploration of visuality? Finally, 'the gaze' may not necessarily be straightforwardly visual, and the chapter pursues the connection between vision and the other senses in Apollonius book 4.